2007
DOI: 10.1111/j.1600-0447.2006.00911.x
|View full text |Cite
|
Sign up to set email alerts
|

Neurocognitive indices of executive hypercontrol in obsessive–compulsive disorder

Abstract: Obsessive-compulsive patients exhibit an impairment of executive functions, especially when tasks also require visuospatial abilities. The impairment might reflect a hyperactivity of the executive control.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
24
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(30 citation statements)
references
References 57 publications
6
24
0
Order By: Relevance
“…Set shifting, or attentional set shifting, is the ability to continuously disengage from irrelevant stimuli or information while engaging in relevant task features. Some studies found that individuals diagnosed with OCD exhibit deficiencies on tasks requiring set shifting, such as the Wisconsin Card Sorting Test (WCST), especially with regards to perseverative errors (Aigner et al, 2007;Bucci et al, 2007;Okasha et al, 2000;Tukel et al, 2012), as well as on the Trail Making Test Part B (TMB; Burdick, Robinson, Malhotra, & Szeszko, 2008;N. Hashimoto et al, 2011;T.…”
Section: Neurobiology Of Ocdmentioning
confidence: 98%
“…Set shifting, or attentional set shifting, is the ability to continuously disengage from irrelevant stimuli or information while engaging in relevant task features. Some studies found that individuals diagnosed with OCD exhibit deficiencies on tasks requiring set shifting, such as the Wisconsin Card Sorting Test (WCST), especially with regards to perseverative errors (Aigner et al, 2007;Bucci et al, 2007;Okasha et al, 2000;Tukel et al, 2012), as well as on the Trail Making Test Part B (TMB; Burdick, Robinson, Malhotra, & Szeszko, 2008;N. Hashimoto et al, 2011;T.…”
Section: Neurobiology Of Ocdmentioning
confidence: 98%
“…Previous findings in this area are, however, inconsistent. Some studies find a positive association between severity of OCD symptoms and neuropsychological performances (Abramovitch, Dar, Schweiger, & Hermesh, 2011;Lacerda et al, 2003;Segalàs et al, 2008), whereas other researchers find no association (Bolton et al, 2000;Bedard, Joyal, Godbout, & Chantal, 2009;Bucci et al, 2007;Deckersbach, Otto, Savage, Baer, & Jenike, 2000).…”
mentioning
confidence: 95%
“…We observed a linear relationship between increased global alpha power over the five-week intervention and decreased cognitive complaints across post-intervention visits. Although our qEEG analyses were exploratory and small in sample size, it is notable that alpha power has previously been linked to level of cognitive function (Bucci et al 2007;Hogan et al 2003). In a study of the neurotoxic effects of chemotherapy in BCS, asymmetry of the alpha rhythm of ≥0.5 Hz was found in 7 of 17 patients who were treated with high doses of chemotherapy and in 2 of 16 patients who underwent standard doses of chemotherapy (Schagen et al 2001).…”
Section: Remember If You Get Lost Stop and Ask Yoursef "What Am I Domentioning
confidence: 94%